EBSD characterization of selected laser melted 316L stainless steel - Muhammad Shafiq Omar (Nanyang Technological University, 2022)
Additive Manufacturing (AM) involves depositing material layer by layer to create products as opposed to traditional manufacturing processes which uses subtraction method such as machining and milling to remove material to get the desired product shape. Advancements in AM have allowed the production of more complex parts and components in relatively short time. Selective Laser Melting (SLM) is a variation of AM that is widely used and will be discussed in this paper. Electron Back-Scatter Diffraction (EBSD) is an important technique which utilises the captured diffraction patterns of electrons from crystals to obtain the grain crystallographic orientations and morphology. These data captured allows the characterisation of materials through analysing the microstructures and correlate the data to the corresponding material properties. Sample preparation methods were also described to ensure that diffraction patterns were able to be captured. Through this technique, a comparison between wrought and SLM-ed 316L stainless steel was made through analyses of the microstructures obtained from OM, SEM and EBSD. It is found that SLM results in longer, epitaxial grains to be observed and leads to finer grain sizes which in turn leads to more improved mechanical properties such as strength. Also, Vickers microhardness tests are conducted and SLM of the sample leads to increased average microhardness value of 219.04 HV while wrought 316L has an average value of 198.76 HV.